National School-Based Health Lifestyles Intervention in Chinese Children and Adolescents on Obesity and Hypertension - Dong, Yanhui; Zou, Zhiyong; Wang, Haijun; Dong, Bin; Hu, Peijin; Ma, Yinghua; Song, Yi; Ma, Jun (Frontiers in Pediatrics, 2021)
Introduction: To examine the effectiveness of the national school-based intervention on both obesity and high blood pressure in Chinese children and adolescents aged 6-18 years. Methods: The national school-based cluster nonrandomized controlled trial was done in seven provinces from September 2013 to February 2014. A total of 23175 children and adolescents in the control group and 25702 in the intervention group were in this trial with a mean follow-up of 6.7±0.9 months. Mixed-effects regression models were used to evaluate the effect of the intervention on body weight and blood pressure (BP). Results: A significant upward in body mass index (BMI) levels, but downward in systolic BP (SBP), diastolic BP (DBP), BMI Z-scores, SBP Z-scores, and DBP Z-scores were witnessed in the intervention group, compared to those in the control group (<0.001). Subgroup analyzes presented significant intervention effects in children aged 6-12 years for BMI, SBP, DBP, and their standardized values Z-Scores, but no effective results were found in adolescents aged 13-18 years. Stratification analyses based on the dynamic weight changes presented non-differential HBP, SHBP, and DHBP prevalence gaps between the control and intervention groups. Children aged 6-12 years with higher BMI percentiles at the baseline presented obvious declines in SBP and DBP standardized values Z-Scores. Conclusion: A mean 6-month multi-centered school-based comprehensive obesity intervention in China yields a small to null effect on obesity and hypertension with age increasing, the early age before 12 years may be the key period for intervention and the younger the better. Precise and high-intensity interventions targeting the population at different stages of childhood and adolescence are urgently needed to develop.